Influence of Marketing Elements Via Social Networks on the Brand Image: A Field Study of a Sample of Mobilis Clients in Algeria - Ahmed, Mire (The Arab Journal of Administration, 2020)
The translational role of social networks as a tool for social communication between individuals in society has been surpassed, it takes a good place in the development of policies and marketing strategies of modern companies, these social networks which have compensated for many others media such as television, radio, etc., and because institutions have become aware of the status of networks in human life, they have used these networks as a means of satisfying customers and to meet their needs, desires and of solving their problems on the one hand, and on the other hand to improve the brand image in their mind. Our study aims to identify the impact of elements of marketing via social networks on the ‘Mobilis’ brand image in Algeria and to know the role that social networks can play in brand marketing.